Perfil de resistencia antibiótica de Escherichia coli y Klebsiella sp. Aisladas de Periplaneta americana en un centro hospitalario y en domicilios de la ciudad de Iquitos, Iquitos-Perú, 2018 - Garcia Pinedo, Julio Cesar Grimaldo (2022)
Cockroaches are disease-transmitting arthropods that can act as mechanical vectors and/or natural reservoirs of pathogens. Their presence in homes and hospitals is worrying in view of their enormous capacity for proliferation and distribution. The objective of this research was to know the antibiotic resistance profile of Escherichia coli and Klebsiella sp isolated from Periplaneta americana (cockroach), in the middle of 2018. The samples were analyzed and identified in the Microbiology Laboratory of the Research Center of UNAP Natural Resources. A total of 25 cockroaches were captured, 15 in the hospital and 10 in the homes, of which 100 strains were obtained between the external and internal part of the cockroaches, 60 strains were from the Iquitos Hospital and 40 strains from the homes. Using a differential identification method (Triple Sugar Iron Agar, Mobility-Indole-Ornithine and CITRATE) and cultures on MacConkey agar, Trypticase Soy Agar and Mueller Hinton, 53 strains of Escherichia coli and 47 strains of Klebsiella sp. The resistance profile evaluated by the agar diffusion method showed a high resistance to colistin of 91% for Klebsiella sp and 72% for Escherichia coli; lower resistance was found for azithromycin with 15% for Escherichia coli and 13% for Klebsiella sp. We show that cockroaches are excellent carriers of pathogenic bacteria and resistant to antibiotics such as colistin, which cause disease in humans. Its presence in a hospital center would be a high risk for public health, where the highest percentage of bacteria resistant to antibiotics was found.